2019
DOI: 10.9734/jpri/2019/v31i130291
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Students’ Knowledge and Perceptions about Antimicrobial Stewardship

Abstract: Introduction: Antibiotic resistance is considered one of the serious threats to global public health. Antimicrobial stewardship programs should be implemented by all hospitals to improve antimicrobial use. It is important that pharmacy students have a sound knowledge of antimicrobial stewardship. Objective: The aim of this study was to determine pharmacy students’ knowledge and perceptions about antimicrobial stewardship. Methodology: The study included a questionnaire that was used to assess the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 15 publications
(12 reference statements)
3
6
1
Order By: Relevance
“…A total of 92.9% disagreed with involving only doctors in antimicrobial stewardship, with 97.8% indicating that pharmacists have a key role to play in AMS and 98.5% indicating that knowledge of AMS is important in their pharmacy careers. Results from this study correlate with that of other studies in which 99% of master of pharmacy students in the United States, 94% of doctor of pharmacy students in the United States, 98.5% of pharmacy students in South Africa, 100% of pharmacy students in Saudi Arabia, and 92% of medical students indicated that good knowledge on antimicrobials prescribing is relevant in their careers (Abbo et al, 2013;Justo et al, 2014;Burger et al, 2016;Inácio et al, 2017;Ahmed et al, 2019).…”
Section: Popoola Et Alsupporting
confidence: 87%
See 1 more Smart Citation
“…A total of 92.9% disagreed with involving only doctors in antimicrobial stewardship, with 97.8% indicating that pharmacists have a key role to play in AMS and 98.5% indicating that knowledge of AMS is important in their pharmacy careers. Results from this study correlate with that of other studies in which 99% of master of pharmacy students in the United States, 94% of doctor of pharmacy students in the United States, 98.5% of pharmacy students in South Africa, 100% of pharmacy students in Saudi Arabia, and 92% of medical students indicated that good knowledge on antimicrobials prescribing is relevant in their careers (Abbo et al, 2013;Justo et al, 2014;Burger et al, 2016;Inácio et al, 2017;Ahmed et al, 2019).…”
Section: Popoola Et Alsupporting
confidence: 87%
“…Some of these interventions include raising awareness of AMR, establishing appropriate evidence-based antimicrobial prescribing, formulary restrictions, restrictive antimicrobial use, infection prevention and control, AMR surveillance, reporting and monitoring, professional education, regulating antimicrobial marketing and advertising, and research into new diagnostic tools, vaccines and antimicrobials (WHO, 2015; Antimicrobial stewardship from principles to practice, 2018; Majumder et al, 2021). These interventions should be implemented in all health care facilities, including community pharmacies, outpatient clinics and nursing homes (Antimicrobial stewardship from principles to practice, 2018; Ahmed et al, 2019). When asked about the purchase of antibiotics, 89.9% of respondents agreed/strongly agreed that antibiotics should not be purchased without a prescription and 81.1% agreed/strongly agreed to restrict the use of selected antimicrobials to preserve their efficacy.…”
Section: Popoola Et Almentioning
confidence: 99%
“… 14 , 15 In addition, a lot of the study’s’ respondents could identify measures that could be used to combat antimicrobial resistance. Other studies, 14 , 20 have also reported similar findings. Despite this, several of our respondents demonstrated significant knowledge gaps with respect to AMR.…”
Section: Discussionsupporting
confidence: 76%
“…However, majority of these respondents could correctly identify AMS’s goals, scope, objectives, the role of pharmacists with respect to AMS and members of the AMS team. Different findings were reported from a study by Ahmed et al, 20 where most of their study population was also not aware of the concept of antimicrobial stewardship, likely due to its lack of inclusion in their curriculum. Another study conducted in South Africa by Burger et al however reported that most of their study population were aware of the AMS concept and could identify the goals of AMS.…”
Section: Discussioncontrasting
confidence: 69%
“…In Australia, one survey [39] has shown that more than 80% of veterinary students, while another study [74] has shown that more than 60% of them perceived that statement. Contrary, in Nigeria a very low percentage of veterinary students (13.1%) [75] and veterinarians (17.1%) [76] have heard about AMS, as well as only about 24% of pharmacy students in Saudi Arabia [77]. Having appropriate knowledge on AMS at the undergraduate level could insure AMS implementation in future work of veterinarians.…”
Section: Plos Onementioning
confidence: 99%